Ragam, Problematika dan Masa Depan Tafsir Al-Quran Digital - Syarif Hidayat (SALIHA: Jurnal Pendidikan & Agama Islam, 2022)
This paper examines the variety of Digital Tafsir al-Qur'an, what problems exist around changing the form of print interpretation to Digital Tafsir al-Qur'an and what the future of Digital Qur'anic interpretation. The data in the study were collected through observation and documentation. The data then descriptive qualitative factual analysis, it meaning that the data is translated according to the facts in the field to obtain a more real picture related to the variety, problems and future of Digital Tafsir-al-Qur'an. The results of the study concluded that there are various digital interpretations of the Qur'an, which can be distinguished from the platform and content. Judging by the platforms, there are those based on Mobile Applications, Web and Computer Applications. In its development, the mobile phone application dominates. There are several things that need attention regarding the problems surrounding Digital Qur'anic Tafsir, including that there is no institution that specifically verifies the validity of changing the printed form into a Digital Qur'anic Tafsir. Most of the Digital Tafsir al-Qur'an does not include a clear source of printed and published interpretations that they quote. Digital interpretation of the Qur'an, most of which have an unfriendly appearance. Most of the Digital Qur'anic Tafsir developed is still very minimal in features. For the purposes of writing scientific papers, most of the Digital Tafsir al-Qur'an does not include reference information in the original book, meaning that when researchers use the application and quote parts of certain interpretations, researchers cannot find where the quotations are in the primary source book. In the future, more and more Digital Qur'anic Tafsir will appear and be developed because they are in demand because of the ease of access. Digital interpretation of the Qur'an that is developed will certainly appear more and more features that are needed by users. Future technology, namely metaverse/virtual lab will also influence the development of this Digital Qur'anic Tafsir.